Negotiating work and family: lifestyle migration, potential selves and the role of second homes as potential spaces. Issue 1 (2nd January 2016) - Hoey, Brian A.
Abstract : This article is based on ethnographic research conducted in the USA with migrants who use an act of relocation as a means of deliberately constructing identity as well as seeking greater 'balance' and 'control' in their lives. Specifically, it examines how 'second' homes can serve as a transitional or 'potential space' in the lives of these migrants not only between different geographic places but also what are taken to be distinct identities and ideals associated with these places and the lives lived in them. Such behaviour is not simply about coping and adapting to a new environment; rather, it is about using qualities of destination places to reconcile different visions of self and family purposefully set apart by relocation and a particular notion of 'the good' that underlies a 'lifestyle commitment' attached to the new place. The author highlights how research into the changing dynamics of work and family can help us understand, generally, effects of an emergent, economic order on working families and, specifically, how associated social and cultural changes shape this migration behaviour. Through analysis of lifestyle migration, this article contributes to discussion of the ways in which cultural values of work and family interrelate in migrancy as well as of challenges and opportunities facing migrants who purposefully attend to leisure activities and places associated with leisure as proper domains for essential identity work and to lifestyle as the means of realising what we may call the 'potential self'.